2012
DOI: 10.1177/0954411911435592
|View full text |Cite
|
Sign up to set email alerts
|

Fluid, solid and fluid–structure interaction simulations on patient-based abdominal aortic aneurysm models

Abstract: This article describes the use of fluid, solid and fluid-structure interaction simulations on three patient-based abdominal aortic aneurysm geometries. All simulations were carried out using OpenFOAM, which uses the finite volume method to solve both fluid and solid equations. Initially a fluid-only simulation was carried out on a single patient-based geometry and results from this simulation were compared with experimental results. There was good qualitative and quantitative agreement between the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, the usage of FV analysis in CSM is becoming increasingly popular due to the attractively simple yet strongly conservative nature of the method. At present, the FV method has been applied to a large range of stress analysis problems in linear-elasticity [1,2,3,4,5,6,7,8], thermo-elastoplasticity [9], thermo-viscoelasticity [10], incompressible elasticity [11,12], contact mechanics [14,15,16,17,18], fracture mechanics [19,20,21,22,23,24,25,26,27,28,29,30,31,32] and fluid-structure interactions [27,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…However, the usage of FV analysis in CSM is becoming increasingly popular due to the attractively simple yet strongly conservative nature of the method. At present, the FV method has been applied to a large range of stress analysis problems in linear-elasticity [1,2,3,4,5,6,7,8], thermo-elastoplasticity [9], thermo-viscoelasticity [10], incompressible elasticity [11,12], contact mechanics [14,15,16,17,18], fracture mechanics [19,20,21,22,23,24,25,26,27,28,29,30,31,32] and fluid-structure interactions [27,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Lantz et al investigated the WSS in a Magnetic Resonance Imaging (MRI)-based subject-specific human aorta, using both FSI and rigid wall models, and found that the influence of wall motion is low on time-averaged WSS and OSI, but when regarding instantaneous WSS values the effect from the wall motion is clearly visible [36]. Kelly et al performed fluid, solid, and FSI simulations on three patient-based abdominal aortic aneurysm geometries [37]. They concluded that solid stress simulations are adequate to predict the maximum stress in an aneurysm wall, while FSI simulations should be performed if accurate prediction of the WSS is necessary.…”
Section: Discussionmentioning
confidence: 96%
“…Traditionally, the impact of wall shear stress has been ignored, as studies in the thoracic aorta have shown it to be several orders of magnitude lower than static stresses calculated using pressure-deformation analyses [19]. Simulations using fluid-structure interactions that combine both fluid flow and solid stress have shown conflicting results in AAAs, with some studies claiming less than 5% impact on peak stress [24] and others reporting more significant increases, on the order of 20% [25]. The impact of fluid-structure interactions in TAAs represents an area of future research.…”
Section: Commentmentioning
confidence: 99%